Katzung's basic & clinical pharmacology - Vanderah, Todd W.; Katzung, Bertram G. (New York : McGraw Hill, 2024)
"To be as clinically relevant as possible, the book includes sections that specifically address the clinical choice and use of drugs in patients and the monitoring of their effects, along with case studies that introduce clinical problems. Each chapter opens with a case study, covers drug groups and prototypes, and closes with summary tables and diagrams that encapsulate important information. Updated to reflect the latest research, this sixteenth edition features a new chapter on cannabinoids, USMLE-style questions, new drug tables, and more."--
Preface -- Basic principles -- Autonomic drugs -- Cardiovascular-renal drugs -- Drugs with important actions on smooth muscle -- Drugs that act in the central nervous system -- Drugs used to treat diseases of the blood, inflammation, & gout -- Endocrine drugs -- Chemotherapeutic drugs -- Toxicology -- Special topics -- Appendix
"A Lange medical book"
Includes bibliographical references and index
Keywords: Pharmacology; Clinical pharmacology; Pharmacology; Pharmacology, Clinical